Transformation of the financial sector role in sustainable development achieving - Shkodkina, Y. M.; Danabayeva, R. I. (Journal of Economic Research & Business Administration, 2015)
Nowadays, domination of the financial sector of economy is a characteristic tendency of the world economic development. The growth rate of the financial capital excels the rates of industrial production, product exchange and consumption. At the same time, the financial sector remained an indirect participant in the process of achieving sustainable development goals, in spite of the commonly recognized necessity of complex and holistic approach to ecological problem solving. Modern trends in achieving sustainable development indicate the change of the role of financial sector. World financial system directs finances towards sustainable development through the adoption of ecological responsibility mechanisms in financial organizations. This paper represents comparison and analysis of such mechanisms. Factors of integration of environmental responsibility principles into financial sector of a country economy are also marked out.